Impact of Block Length and Temperature over Self-Assembling Behavior of Block Copolymers. (24th April 2016) - Kosa, Samia A.; Al-Harbi, Laila M.; Baloch, Musa Kaleem; Ullah, Irfan; El-Mossalamy, Elsayed H.
Abstract : Self-assembling behavior of block copolymers having water-soluble portion as one of the blocks plays key role in the properties and applications of the copolymers. Therefore, we have synthesized block copolymers of different block length and investigated their self-assembling behavior with reference to concentration and temperature using surface tension and conductance measurement techniques. The results obtained through both techniques concluded that critical micelles concentration (CMC) was decreased from 0.100 to 0.078 g/dL with the increase in length of water insoluble block and 0.100 to 0.068 g/dL for the increased temperature. Δ G m i c was also decreased with the increase in temperature of the system, concluding that the micellization process was encouraged with the increase in temperature and block length. However, Δ H m i c values were highest for short block length copolymer. The surface excess concentration obtained from surface tension data concluded that it was highest for short block length and vice versa and was increased with the increase in temperature of the system. However, the minimum area per molecule was largest for highest molecular weight copolymers or having longest water insoluble block and decreases with the increase in temperature.